2017
DOI: 10.1515/cercles-2017-0002
|View full text |Cite
|
Sign up to set email alerts
|

Sequences of normative evaluation in two telecollaboration projects: A comparative study of multimodal feedback through desktop videoconference

Abstract: In our study we analyse how the same interactional dynamic is produced in two different pedagogical settings exploiting a desktop videoconference system. We propose to focus our attention on a specific type of conversational side sequence, known in the Francophone literature as sequences of normative evaluation. More particularly, we analyse data from two telecollaborative projects through desktop videoconference: a French-Chinese tandem, and a French-Irish telecollaboration between trainee teachers and learne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The second are sequences of normative evaluation (hereafter SEN; Py, 2000): another type of side sequence in which the language expert considers that there has been an error in the interlocutor's expression and signals this. 2 Analysis was conducted by replicating the procedure in previous research (Cappellini & Azaoui, 2017). First, the two authors independently identified the conversational phenomena of interest, then discussed any discrepancies until agreement was reached.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The second are sequences of normative evaluation (hereafter SEN; Py, 2000): another type of side sequence in which the language expert considers that there has been an error in the interlocutor's expression and signals this. 2 Analysis was conducted by replicating the procedure in previous research (Cappellini & Azaoui, 2017). First, the two authors independently identified the conversational phenomena of interest, then discussed any discrepancies until agreement was reached.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Yamada and Akahori (2010) manipulated the presence of the video feed of one of the interlocutors to gauge its impact on the other interlocutors' grammatical accuracy correction while speaking. Although this approach has informed some recent studies (Kozar, 2016, for instance), research has more commonly adopted holistic approaches in which multimodality is conceived of as a whole and is studied within paradigms such as multimodal conversation analysis (CA) (Cappellini & Azaoui, 2017;Sert & Balaman, 2018), interactional sociolinguistics (Satar, 2016), social semiotics, or combinations thereof (Helm & Dooly, 2017;Satar & Wigham, 2017). These studies have enhanced our understanding of how multimodality is used as a whole during interaction, often by focusing on particular conversational dynamics such as instruction-giving sequences (Satar & Wigham, 2017, 2020, policing (Sert & Balaman, 2018), or side sequences of negative feedback (Cappellini & Azaoui, 2017).…”
Section: Multimodalitymentioning
confidence: 99%
See 1 more Smart Citation